Design of irrigation scheme for an improved fodder crop production as food for ranch cattle - Flayin, Malum J.; Adgidzi, Donald (Technology audit and production reserves, 2023)
The object of this research is Cattle Ranches. Cattle Ranches is the practice of raising herds of cattle on large landscape including the structures and crops of legumes, grasses or forages, devoted to the raising, and grazing of the herds. Organized animal productions have been successfully practiced for decades in developed countries, but have been of minor Agricultural consideration in arid regions and Sub-Saharan Africa. Most African herders relied on natural pasture in the tropics which are either forested with high incidences of disease and parasites detrimental to profitable animal production, or dry zone which calls for tremendous physical exertion on the animal in order to obtain feed and water. Feed shortage and low quality of available feeds are constraints for livestock production and has been a major constraint for animal production during dry periods. Therefore, farmers use different coping mechanisms ranging from purchasing of feeds from the market and destocking unproductive animals as drastic measures. The negative trend results into many pastoralists resorting to grazing in crops farm lands. The pressure from increasing population and diminishing availability of land for pastoral range practice causes farmers- herders’ clashes which results into loss of lives. Rise in the toll of farmers-herdsmen crisis and clashes across many African countries in recent years, became worst. This brings to fore, the need to set up Cattle Ranches as an alternative to nomadic agriculture. The viability of setting up ranches for Cattles using improved irrigation systems to make up for the dry zone/season condition is practicable and profitable as practiced in developed countries. Ranches provide feed from grown forage legumes and fodder trees species through irrigation, combined with appropriate postharvest handling practices. Feeds availability mitigate the constraints of food scarcity and improves livestock productivity. The study consisted of outlining design procedure for the establishment of an irrigation scheme for an improved fodder crop production as food for ranch cattle.